Mulheres negras na construção do movimento Pan-Africano do início do século XX - Santos, Fernanda Vieira da Silva (2024)
Pan-Africanism was a cultural, philosophical, social, and political movement that sought to unify the Black diaspora and advocate for their return to the African continent. Prominent figures such as W.E.B. Du Bois, Kwame Nkrumah, and George Padmore are widely recognized within this movement. However, lesser-known contributors, including Addie Waites Hunton, Ida Alexander Gibbs Hunt, and Amy A. Garvey, remain underrepresented in historical narratives. This research aims to systematize their participation and highlight their contributions to Pan-Africanism. The central hypothesis posits that these women made significant contributions to the movement, particularly within the academic and political domains of Black feminism. Grounded in the theoretical perspectives of Collins (2016) and Perry (2009), this study examines the marginalization of Black women in intellectual discourse and their political engagement in such movements. The life trajectories of Addie, Ida, and Amy provide a foundation for reflecting on these themes. Methodologically, the study adopts an approach likened to embroidery, stitching together narratives that position these women as pivotal actors in the Pan-African movement. This process reconstructs the "framework" of their historical presence and significance. In conclusion, the findings reveal that these women played indispensable roles in the development of Pan-Africanism. They articulated a distinct perspective that interconnected race, gender, and class in the broader struggle for political and cultural liberation. This research contributes to the field of diaspora studies and Black agency by integrating their overlooked contributions into the larger narrative of Pan-Africanism.